2008
DOI: 10.1111/j.1467-9280.2008.02098.x
|View full text |Cite
|
Sign up to set email alerts
|

The Representation of Simple Ensemble Visual Features Outside the Focus of Attention

Abstract: The representation of visual information inside the focus of attention is precise relative to the representation of information outside the focus of attention. We find that the visual system can compensate for the cost of withdrawing attention by pooling noisy local features and computing summary statistics. The location of an individual object is a local feature, while the center of mass of several objects (centroid) is a summary feature representing the mean object location. Three Experiments showed that wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
382
5
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(421 citation statements)
references
References 21 publications
33
382
5
1
Order By: Relevance
“…Cohen and Dennett emphasized gist and ensemble representations as well as generic representations [29]. One illustration of gist/ensemble representations was provided by Alvarez [51], who showed that when subjects track 4 moving disks they also are aware of the 'center of mass' of 4 distractor disks. For simplicity, I will lump gist-like and generic perception together under the heading of generic representation.…”
Section: Generic Consciousness Combined With Unconscious Iconic Memorymentioning
confidence: 99%
“…Cohen and Dennett emphasized gist and ensemble representations as well as generic representations [29]. One illustration of gist/ensemble representations was provided by Alvarez [51], who showed that when subjects track 4 moving disks they also are aware of the 'center of mass' of 4 distractor disks. For simplicity, I will lump gist-like and generic perception together under the heading of generic representation.…”
Section: Generic Consciousness Combined With Unconscious Iconic Memorymentioning
confidence: 99%
“…It was argued that these estimates (e.g., eight objects for the centroid, and seven for faces) exceeded the expected limits of object-based parallel attention (Oksama & Hyönä, 2004;Pylyshyn & Storm, 1988;Scholl, 2001), suggesting that subjects did not rely on this type of object-based sampling strategy. Because previous methods have relied on the observed discrimination thresholds or response variability when subjects must represent, for instance, the size of a single item as a way of estimating the internal noise that might affect ensemble processing (Alvarez & Oliva, 2008;Haberman & Whitney, 2009, 2010, the question of whether the internal noise that affects ensemble representation is lower than the internal noise that affects individual-object representation has not yet been tested. The opportunity has arisen to use variance summation modeling to estimate both the internal noise and the sample size that affect ensemble feature processing from within the ensemble feature task itself.…”
mentioning
confidence: 99%
“…This summary representation or statistic has been called an "ensemble feature." For example, laboratory experiments suggest that humans can represent with little effort the mean size (Ariely, 2001;Chong & Treisman, 2003;Im & Chong, 2009), general direction of motion (Watamaniuk & Duchon, 1992), general location or "centroid" (Alvarez & Oliva, 2008), and approximate number of items in a group (Halberda, Sires, & Feigenson, 2006), as well as the average emotion of faces in a crowd (Haberman & Whitney, 2009, 2010.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, just as one averages stimuli far away from the focus of attention in visual perception, one similarly averages stimuli "far away" (i.e., the future rewards of late decision steps) from the current focus of decision in multistep decision making. In line with this proposal, humans can extract ensemble statistics from a variety of features and stimuli, including size (21,22), speed (23), position (24), spatial orientation, and frequency, even under reduced attention (25). Furthermore, ensemble averaging is not limited to low-level perceptual stimuli.…”
Section: Discussionmentioning
confidence: 90%